(untitled) (Texas Journal of Medical Science, 2023)
The most important radiation accidents and incidents are considered from the point of view of the significance of risk factors of such events. The priority of the "human factor" in the occurrence and development of radiation events of any type is noted. Taking into account the nature of radiation incidents and the degree of significance of risk factors, a system of urgent measures in case of their occurrence is proposed